Respuesta :
Hi there!
To convert this equation into slope intercept form before graphing it, we need to put it into this form:
y = mx + b
So, first, we should move the 2x to the right side of the equation by subtracting 2x from both sides.
y = -2x + 6
and then, you graph.
Hope this helps!
To convert this equation into slope intercept form before graphing it, we need to put it into this form:
y = mx + b
So, first, we should move the 2x to the right side of the equation by subtracting 2x from both sides.
y = -2x + 6
and then, you graph.
Hope this helps!
So, to graph this thing, you must put it in terms of y (at least, that's convention). So, let's isolate y:
[tex]2x-2x+y=6-2x[/tex]
[tex]y = 6-2x[/tex]
Rearrange the equation so it's easier to graph (i.e. put it in slope-intercept form):
[tex]y = -2x + 6[/tex]
From this, we can understand that the graph intercepts the y-axis at 6, and the slope is -2.
[tex]2x-2x+y=6-2x[/tex]
[tex]y = 6-2x[/tex]
Rearrange the equation so it's easier to graph (i.e. put it in slope-intercept form):
[tex]y = -2x + 6[/tex]
From this, we can understand that the graph intercepts the y-axis at 6, and the slope is -2.